ANALYSIS OF GENE EXPRESSION IN BLOOD AS AN ADDITIONAL TOOL TO MONITOR METHOTREXATE THERAPY IN PATIENTS WITH RHEUMATOID ARTHRITIS - Elena Vasilyevna Chetina; N V Demidova; D E Karateev; E L Nasonov (Научно-практическая ревматология)
Objective. To assess the changes in clinical, immunological, X-ray indicators and expression of the mTOR (mammalian target of rapamycin) genes, the key regulator of cell growth and proliferation; ULK1 (autophagy marker); р21 (cyclindependent kinase inhibitor); caspase 3 (indicator of apoptotic activity); MMP9 (matrix metalloproteinase 9) and cathepsin K, which participate in joint destruction, and proinflammatory cytokine TNFα (tumor necrosis factor α) in blood of patients with rheumatoid arthritis (RA) receiving methotrexate (MT) therapy.Materials and Methods. Thirty-three RA patients (21 with positive and 12 with negative rheumatoid factor (RF), respectively; median age, 47.1 years) and 28 healthy volunteers (median age, 45.1 years) were examined. All patients have been receiving MT for 2 years. The clinical response was assessed according to the DAS28 score. ESR and the serum levels of anti-cyclic citrullinated peptide antibodies (ACPA), C-reactive protein (CRP), and RF were also determined. Degenerative changes in the joints were evaluated by X-ray examination. Gene expression was measured in peripheral blood cells using reverse transcriptase reaction and real-time polymerase chain reaction.Results. MT therapy considerably reduced the disease severity according to DAS28 score, as well as the number of swollen and painful joints both in seropositive (RF+) and seronegative (RF-) RA patients. Ten patients reached remission by the end of the study. In (RF-) RA patients, the absence of progression of joint destruction was accompanied by the absence of any significant changes in expression of MMP9 and cathepsin K, as well as a stronger suppression of TGFα (its expression became comparable to that in the control group). Patients who achieved remission showed a significant decrease in the expression level of the cathepsin K gene as compared to that at the start of the study. In (RF+) RA patients, MT therapy significantly reduced the clinical and immunological indicators; however, the increased number of erosion sites and further joint space narrowing was observed. It was accompanied by a considerable increase in the expression levels of the MMP9, cathepsin K, and TGFα genes as compared to those in healthy individuals.Conclusions. The changes in expression of the genes responsible for destruction of the hyaline cartilage and bone matrix (MMP9 and cathepsin K) and the TGFα level in blood of RA patients due to MT therapy correlate with the changes in clinical, immunological, and X-ray parameters used to evaluate patient's condition in clinical practice.